Attitudes and Beliefs towards Rotavirus Vaccination in a Sample of Italian Women: A Cross-Sectional Study - Giuseppe Di Martino; Riccardo Mazzocca; Laura Camplone; Fabrizio Cedrone; Pamela Di Giovanni; Tommaso Staniscia (Vaccines, 2023)
(1) Background: Rotavirus is the leading cause of severe diarrhea and dehydration in infants and young children worldwide. Despite the proven benefits of vaccination, vaccine hesitancy and refusal remains a significant barrier to achieving high vaccination coverage in many countries, such as Italy. (2) Methods: An online survey was conducted among women aged between 18 and 50 years from Abruzzo Region, Italy. The survey was composed of two main sections: demographic characteristics and attitudes and knowledge about rotavirus vaccination, based on a five-point Likert scale. Logistic regression analysis was performed to evaluate factors associated with willingness to get the rotavirus vaccination. (3) Results: A total of 414 women were enrolled in the study. Women who were unaware of rotavirus more frequently had a lower education level (university degree 62.5% vs. 78.7%, p = 0.004) and reported having no children (p < 0.001). About half of the enrolled women thought that rotavirus infection is dangerous (190, 55.6%) and that rotavirus can cause a serious illness (201, 58.8%). Regarding associated factors, women informed by a physician were more likely get a vaccination compared to women informed by friends or relatives (OR 34.35, 95% CI 7.12–98.98, p < 0.001). (4) Conclusions: The present study showed low levels of knowledge and attitudes towards rotavirus vaccination. These results highlight the need for developing and improving additional public education programs for parents.